(untitled) (Development Service Industry Management, 2024)
The article examines theoretical and applied aspects of risk management at different stages of the organization’s life cycle. It is proven that the risks that accompany the organization’s activities at different stages of its life cycle cause the emergence of numerous threats to the enterprise’s activities. The essential characteristics of the categories "risk" and "life cycle" are considered. The characteristic features of the main stages of the organization’s life cycle are determined and structured. A general scheme for identifying enterprise risks is presented. The most characteristic risks at different stages of the life cycle are determined and structured, as well as the corresponding methods that will allow them to be identified. It is substantiated that risk management is based on a purposeful search and organization of systematic work to reduce risk in an uncertain market situation. It is noted that in order to increase the effectiveness of the risk management system at different stages of the life cycle, it is necessary to adhere to the relevant principles. It is determined that systemic risk management is a multi-stage process aimed at reducing or optimizing the losses of the enterprise in risky situations. The main stages of implementing a risk management system at an enterprise are described. It is proven that taking into account the entire complex of risks that accompany the operational activities of each market entity is an extremely necessary step for further functioning and sustainable development.